2017
DOI: 10.1515/pp-2016-0028
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for pathological diagnosis on biopsy samples from peritoneal dialysis patients

Abstract: Peritoneal dialysis (PD) has been established as an essential renal replacement therapy for patients with end stage renal disease during the past half century. Histological evaluation of the peritoneal membrane has contributed to the pathophysiological understanding of PD-related peritoneal injury such as peritonitis, fibrosis, and encapsulating peritoneal sclerosis (EPS). Hyalinizing peritoneal sclerosis (HPS), also known as simple sclerosis, is observed in almost all of PD patients. HPS is morphologically ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 104 publications
0
9
0
Order By: Relevance
“…in PD. Currently, biopsy is a golden standard to evaluate peritoneal changes in humans, which can be limited by size and sampling positions of the evaluated regions [26,27]. Although it was recently demonstrated that an ultrasound based examination of peritoneal membrane thickness is possible [28], it is inaccurate and requires experienced personnel.…”
Section: Discussionmentioning
confidence: 99%
“…in PD. Currently, biopsy is a golden standard to evaluate peritoneal changes in humans, which can be limited by size and sampling positions of the evaluated regions [26,27]. Although it was recently demonstrated that an ultrasound based examination of peritoneal membrane thickness is possible [28], it is inaccurate and requires experienced personnel.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5] The main characteristics of chronic peritoneal injury include loss of mesothelial cells, submesothelial thickness, accumulation of extracellular matrix and neoangiogenesis, which ultimately lead to ultrafiltration failure (UFF). 4,6 Therefore, it is necessary to explore effective methods for the early assessment of peritoneal injury and dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that ultrafiltration failure occurs only in the advanced stages of peritoneal fibrosis, PET data in clinical practice might be available too late to monitor peritoneal function. Although invasive peritoneal biopsy could be used for the pathological diagnosis of PD-related peritoneal injury, the results do not reflect global peritoneal structural changes [ 9 , 10 ]. Thus, it is highly desirable to establish suitable biomarkers and therapeutic targets for disease progress prediction and to allow patients to improve their survival during long-term PD.…”
Section: Introductionmentioning
confidence: 99%